Studi Literatur Review: Pengaruh Profitabilitas, Audit Complexity dan Kualitas Audit Terhadap Audit Report Lag - Hayatun Ruwaidha; Trinandari Prasetya Nugrahanti (International Forum of Researchers and Lecturers, 2024)
Background: Financial reports are considered important for the final accounting process which is a means of financial communication and accountability to stakeholders for decision making for the next period. This study aims to analyze and obtain empirical evidence of influence by producing articles to review the effect of profitability, audit complexity and audit quality on audit report lag. The research methodology used in this research is the literature review method, using qualitative research methods where the articles analyzed in this article are 21 article writings, consisting of 5 international and 16 national journals which have been selected according to the keywords analyzed and their searches using google scholar with quantitative and qualitative research designs. The review results Profitability affects Audit Report Lag. Companies that have a good level of profitability try to avoid delays in the audit process because these delays can be considered bad news and become public conversation. Audit Complexity affects Audit Report Lag, because companies with high operating complexity and more subsidiaries will tend to complete their audits longer. The effect of Audit Quality on Audit Report Lag, because the higher the quality of a company's KAP, the faster the audit report can be completed. Conclusion: Profitability, Audit Complexity and Audit Quality have a significant effect on Audit Report Lag. Audit Report Lag can have an unfavorable effect on future business because it can hinder decision making for the next period and affect other aspects.